PENGARUH RISIKO PASAR, RISIKO KREDIT, DAN RISIKO LIKUIDITAS TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2020 - Andri Irawan; Ronatry Stiawati; Maulana Hadi Kusuma (Jurnal Manajemen Bisnis Unbara, 2022)
ABSTRACT Ronatry Stiawati (2022). The Influence of Market Risk, Credit Risk, and Liquidity Risk on Financial Performance in State-Owned Banking Companies Listed on the Indonesia Stock Exchange for the 2015-2020 Period. This study aims to examine the influence of market risk, credit risk, and liquidity risk on the financial performance of state-owned banking companies listed on the Indonesia Stock Exchange for the 2015-2020 period, either partially or simultaneously. The analytical tool used in this research is multiple linear regression. Based on the results of the analysis and discussion, it is concluded that partially market risk variable (X1) has a positive and significant influence on financial performance (Y), credit risk variable (X2) has a negative and significant influence on financial performance (Y), and liquidity risk variable (X3). Noinfluence, no significant and negative direction on financial performance (Y). Simultaneous test results show that market risk (X1), credit risk (X2), and liquidity risk (X3) have a significant and positive influence on financial performance (Y). From the results of the coefficient of determination, the percentage of the influence of the independent variable on the dependent variable is 87.9%, while the remaining 12.1% is influenced by other factors not analyzed in this study. Keywords: Market Risk, Credit Risk, Liquidity Risk and Performance Finance.